Environmental Orderliness Affects Self-Control and Creative Thinking: The Moderating Effects of Trait Self-Control - Li, Zhengyan; Liu, Ning; Li, Shouxin (Frontiers in Psychology, 2020)
Environmental orderliness can affect both self-control behaviors and creative thinking, but little research has focused on the moderators of its effects. Consequently, in two experiments, the present research investigated the moderating effect of trait self-control on environmental orderliness influencing both self-control behaviors and creative thinking. In Experiment 1, we explored whether trait self-control could moderate the effect of environmental orderliness on behavioral self-control. Participants exposed to an orderly or a disorderly room were asked to complete a breath-holding task measuring self-control. The results showed that low trait self-control participants were more self-controlled in the orderly environment, while the self-control of those with high trait self-control was not affected by environmental orderliness. In Experiment 2, the moderating effect of trait self-control on environmental orderliness affecting creative thinking was investigated with a picture priming orderliness and the Alternative Uses Test. As expected, participants with high trait self-control in the disorderly environment had better creative thinking performance, although there was no difference in the performance of those with low trait self-control between the two environmental orderliness conditions. The results demonstrated that trait self-control could moderate the dual effect of environmental orderliness. The present study sheds light on the environmental orderliness literature, contributes to the understanding of the common mechanism of the dual effect, and has practical implications for the shaping and cultivation of individuals’ self-control behaviors and creative thinking.